[Mindulani festival [videorecording] Sentrong Pangkultura ng Pilipinas in harmony with the National Commission for Culture and the Arts. - Cultural Center of the Philippines; Philippines. National Commission for Culture and the Arts. (Manila NCCA)
A documentation of the Mindulani festival. Includes performances of the different theater groups in Mindanao.
VHS.
With English subtitles.
Keywords: Festivals -- Philippines -- Mindanao